2017
DOI: 10.5312/wjo.v8.i12.902
|View full text |Cite
|
Sign up to set email alerts
|

Do-Not-Resuscitate status is an independent risk factor for patients undergoing surgery for hip fracture

Abstract: AIMTo determine morbidity and mortality in hip fracture patients and also to assess for any independent associations between Do-Not-Resuscitate (DNR) status and increased post-operative morbidity and mortality in patients undergoing surgical repair of hip fractures.METHODSWe conducted a propensity score matched retrospective analysis using de-identified data from the American College of Surgeons’ National Surgical Quality Improvement Project (ACS NSQIP) for all patients undergoing hip fracture surgery over a 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…9 There are few studies addressing how a DNR/DNI designation may influence prognosis in hip fracture patients. 10 However, one recent study evaluated more than 9000 patients using a national database and found that DNR was independently associated with mortality after surgical treatment of a hip fracture. Many risk factors of postoperative morbidity and mortality after hip fracture surgery are well documented, but almost all studies fail to evaluate or even mention DNR/DNI status.…”
Section: Introductionmentioning
confidence: 99%
“…9 There are few studies addressing how a DNR/DNI designation may influence prognosis in hip fracture patients. 10 However, one recent study evaluated more than 9000 patients using a national database and found that DNR was independently associated with mortality after surgical treatment of a hip fracture. Many risk factors of postoperative morbidity and mortality after hip fracture surgery are well documented, but almost all studies fail to evaluate or even mention DNR/DNI status.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinicians also worry that by recording a DNAR decision, this may compromise other aspects of the patient's care. This is not unreasonable as systematic reviews have shown that surgical patients with DNARs have a worse mortality even when adjusted for other risk factors [12][13][14]. However, analysis has shown that in the hip fracture subgroup, DNAR is not an independent mortality risk factor [15].…”
Section: Discussionmentioning
confidence: 99%
“…To take a similar example, past literature has demonstrated a strong association between do-not-resuscitate (DNR) status and adverse outcomes. [20][21][22][23][24] In all likelihood, the DNR status does not directly cause worse outcomes so much as it marks a sick and vulnerable population. Selection bias at the individual patient level may contribute to an association between comanagement and worse outcomes.…”
Section: Discussionmentioning
confidence: 99%